Modeling International Relationships in Applied General Equilibrium (MIRAGE) Model - International Food Policy Research Institute (International Food Policy Research Institute, 2001)
The MIRAGE (Modeling International Relationships in Applied General Equilibrium) model is a multi-country, multi-sector dynamic model, developed initially at the Centre d'Etudes Prospectives et d'Informations Internationales (CEPII) in Paris (France). Beyond IFPRI and CEPII, the model is now shared with different institutions such as the European Commission DG Trade and DG Enterprise (Brussels, Belgium), French National Institute for Agricultural Research ( INRA, Paris, France), United Nations Economic Commission for Africa (UNECA, Addis Ababa, Ethiopia), and the World Trade Organization (WTO, Geneva, Switzerland). The MIRAGE model has been developed primarily to study trade policy scenario and has been intensively used to assess bilateral and multilateral agreements. As a global CGE, it provides a rich set of indicators for each region that allows measuring the impact of any policy changes. Such indicators include: changes in production, production factor uses, real wages, value added by sector, real GDP, real income, exports, imports, terms of trade. It can be used under different set of assumptions to be easily adaptable to the issue at stake (perfect and imperfect competition, dynamic or static approach, imperfection on labour markets, alternative macroeconomic closures). As a global model, the GTAP 7 database is its main source of information and can cover 113 regions of the world and up to 57 sectors. However, it has been developed in parallel with the MAcMAp-HS6 database that allows a high detailed of trade policy scenario design. When the dynamic features are used, a realistic baseline is built based on United Nations Agencies demographic projection as well as IMF economic growth assumptions.